Short-Term Indoor Radon Gas Assessment in Granitic Public Buildings: A Multi-Parameter Approach - Azevedo, Rolando (2022)
Radon is a naturally occurring radioactive gas formed in the soil with higher predominance in granitic zones. It is a well-known Indoor Air Quality (IAQ) parameter that is measured in higher radon risk zones. The proposed methodology begins with a unidimensional data characterization followed by a multidimensional analysis that will relate radon concentration with other parameters, i.e. Temperature, Relative Humidity, and Indoor Air Pressure. The visual representation of the radon gas concentration variation over the week and throughout the day helped to identify some relevant patterns. A multi-parameter approach was used to analyze the correlation of radon gas concentration with the other parameters, which can be managed to improve the overall IAQ